Історія видання повного зібрання творів та листів Пантелеймона Куліша у листуванні Івана Каманіна до Ганни Барвінок - Якобчук, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
A source study analysis of the complex of letters of I. M. Kamanin to A. M. Kulish (Hanna Barvinok) is carried out in the article. Significance and informative value of this correspondence are determined. The publication process of a part of the complete works of P. A. Kulish is reproduced on the basis of the mentioned letters.